Physics teachers’ conceptions of equity: Access and achievement - Huynh, Tra; Bauman, Lauren C.; Robertson, Amy D.; Scherr, Rachel E. (Frontiers in Education, 2023)
Physics teachers’ definitions of equity inform how they identify inequity and take action to transform it. In this paper, we adapted Gutiérrez’s equity framework from mathematics education research to physics education research. The framework defines equity in terms of four dimensions: access, achievement, identity, and power. We used this equity framework to characterize the equity conceptions shared by 23 teachers who participated in an equity-focused professional development. We found that the access and achievement dimensions of equity are popular with teachers compared to the identity and power dimensions, and that teachers share a common understanding of conceptions of access and achievement in ways that is consistent with educational literature and discourses.